2023
DOI: 10.1021/acscatal.3c03771
|View full text |Cite
|
Sign up to set email alerts
|

Pyridylmethyl Radicals for Enantioselective Alkene Hydroalkylation Using “Ene”-Reductases

Sophie G. Bender,
Todd K. Hyster

Abstract: Aromatic electron-deficient heterocycles, such as pyridines, are found in many biologically relevant structures, including those with medicinal applications. Methods for their substitution can streamline the synthesis of valuable molecules and allow access to unexplored chemical space. However, enantioselective methods for these derivatizations remain lacking, especially at remote stereocenters. Here, we present a photoenzymatic reaction for the reductive coupling of electron-deficient heterocycles with alkene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Thus, GluER-W100F-W342F was identified as the optimal mutant for the scope studies. To the best of our knowledge, the W100F and W342F mutations have yet to be reported in prior photoenzymatic systems. To demonstrate the synthetic utility of the method, the model reaction was scaled up to 1 mmol, and 3a was obtained in 66% yield with 96:4 er (Figure a). Control experiments using DMSO or CH 3 CN instead of THF as the cosolvent resulted in diminished yield and enantiopurity of 3 (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, GluER-W100F-W342F was identified as the optimal mutant for the scope studies. To the best of our knowledge, the W100F and W342F mutations have yet to be reported in prior photoenzymatic systems. To demonstrate the synthetic utility of the method, the model reaction was scaled up to 1 mmol, and 3a was obtained in 66% yield with 96:4 er (Figure a). Control experiments using DMSO or CH 3 CN instead of THF as the cosolvent resulted in diminished yield and enantiopurity of 3 (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…By fine-tuning substituents of the peptide thiol catalysts, Knowles, Miller, and Houk recently reported an elegant asymmetric hydroamination reaction that accommodates acyclic olefins, although a sterically hindered substituent such as tert -butyl is generally required for the enol ester substrates to achieve a high enantioselectivity. Having realized the challenges associated with acyclic olefins using small-molecule catalysts and inspired by previous work on photoenzymatic catalysis, we questioned whether we could develop complementary oxidation-initiated photoenzymatic hydrofunctionalization reactions that are compatible with acyclic olefins and allow the use of easily oxidized radical precursors as the substrate. Herein, we report the realization of such a goal by developing an oxidative photoenzymatic enantioselective hydrosulfonylation of olefins using an engineered gluconobacter ene-reductase (GluER) (Scheme c).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested a series of GluER homologues and discovered that the ERED from G. morbifer (MonstER) could couple 4-(chloromethyl)­pyridine 43 with α-methylstyrene in 71% yield with 94:6 er using violet light (Figure ). In these reactions, the remaining mass balance is the hydrodehalogenated starting material. Presumably, the π-system of chloromethylpyridine enables CT-complex formation without the alkene.…”
Section: Enzyme Selection and Radical Initiation Mechanismsmentioning
confidence: 99%
“…Our group and others previously demonstrated that flavin-dependent “ene”-reductases (EREDs) could catalyze the intermolecular hydroalkylations of olefins using α-halocarbonyl compounds as radical precursors. Building upon these foundational methods has enabled a variety of stereoselective reactions involving the formation of C–C, C–N, , C–O, and C–S bonds . These reactions proceed via the single electron reduction of the alkyl halide by flavin hydroquinone (FMN hq ) to afford a radical intermediate that reacts with the alkene to afford an alkyl radical.…”
mentioning
confidence: 99%